1996
DOI: 10.1093/oxfordjournals.humrep.a019256
|View full text |Cite
|
Sign up to set email alerts
|

Localization and characterization of white blood cell populations within the human ovary throughout the menstrual cycle and menopause

Abstract: The purpose of this investigation was to localize and characterize white blood cell populations in the human ovary through its physiological life cycle. Ovaries from 30 women of reproductive age and from three post-menopausal women were embedded in paraffin or frozen. Clinical information and pathology review were used to obtain accurate menstrual cycle information and to ensure the absence of ovarian disease. Tissue sections were stained for leukocyte phenotypes and the numbers of white blood cells in the ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 17 publications
5
84
1
Order By: Relevance
“…We have also demonstrated direct correlations of ROS generation (Gonz谩lez et al 2006) and activated NF B (unpublished data) with these androgen levels. Infiltration of the ovary by MNC-derived macrophages has been previously reported (Best et al 1996). Ovarian steroidogenic enzymes responsible for androgen production are stimulated by oxidative stress and inhibited by antioxidants, such as statins, in vitro .…”
Section: Discussionmentioning
confidence: 88%
“…We have also demonstrated direct correlations of ROS generation (Gonz谩lez et al 2006) and activated NF B (unpublished data) with these androgen levels. Infiltration of the ovary by MNC-derived macrophages has been previously reported (Best et al 1996). Ovarian steroidogenic enzymes responsible for androgen production are stimulated by oxidative stress and inhibited by antioxidants, such as statins, in vitro .…”
Section: Discussionmentioning
confidence: 88%
“…19 Because the latter interact with HLA molecules, it must be concluded that the MHC complex plays a central role within the immunological integrity of the ovary. Evidence from a number of studies supports the notion that in several tumor systems tumor-infiltrating lymphocytes may represent an active immune response of the host directed against the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In the preovulatory follicle wall, mast cells appear to be absent and the number of T cells as main representatives of the adaptive immune system are low in number (Best et al, 1996;Spanel-Borowski et al, 1997;Bauer et al, 2001). It points to a minor cross-talk between INIM and adaptive immunity.…”
Section: Eosinophils and Tachykinin Expression For Tissue Repair In Imentioning
confidence: 97%
“…Page 11 with the adaptive immunity, whereas augmented T cells in the CL of regression speaks for exchanges between the two immune systems (Best et al, 1996;Spanel-Borowski et al, 1997;Bauer et al, 2001). A disturbed conversation between INIM and adaptive immunity is reflected by altered T cell profiles in the follicular fluid of patients with idiopathic infertility and in ovaries with premature ovarian failure due to autoimmune damage (Lukassen et al, 2003;Vujovic, 2009 (Banchereau and Steinman, 1998;Mellman and Steinman, 2001;Turvey and Broide, 2010), DCs are key players between INIM and adaptive immunity.…”
Section: Clinical Challenges and Summarymentioning
confidence: 99%